1971
DOI: 10.1121/1.1912474
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Position of Discharges in Single Auditory Nerve Fibers within the Cycle of a Sine-Wave Stimulus: Frequency and Intensity Effects

Abstract: Period histograms, which display the distribution of spikes throughout the period of a periodic stimulus, were computed for discharges recorded from single auditory nerve fibers of the squirrel monkey when low-frequency tones were employed. For frequencies up to about 4 kHz, where phase locking is observed, the average phase angle of the discharges was tracked as frequency was varied in small steps from low to high. To a first approximation, the cumulative shift in average phase angle is a linear function of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
132
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(156 citation statements)
references
References 7 publications
23
132
1
Order By: Relevance
“…The nonconstancy of cumulated phase lag with frequency is another demonstration of the failure of scaling invariance mentioned in the discussion of Figure 7 and is consistent with the theoretical analysis of Greenwood (1977) of AN data reported by Anderson et al (1971).…”
Section: Panoramic Phase Analysis In the Apexsupporting
confidence: 76%
“…The nonconstancy of cumulated phase lag with frequency is another demonstration of the failure of scaling invariance mentioned in the discussion of Figure 7 and is consistent with the theoretical analysis of Greenwood (1977) of AN data reported by Anderson et al (1971).…”
Section: Panoramic Phase Analysis In the Apexsupporting
confidence: 76%
“…While some conclusions were consistent with findings in mammals, others were clearly different, in particular, the shape of the STAs and the rate at which the instantaneous frequency of the impulse response changed. Also, we showed that phase-frequency curves at different sound levels did not always intersect at a common point as previously shown in mammals (Anderson et al 1971;Recio-Spinoso et al 2005;Versteegh et al 2011). We discuss the possible meaning of the differences and similarities encountered.…”
Section: Discussionsupporting
confidence: 74%
“…The fact that the hypothesis of exact CF pivoting, which posits that when level changes, the phase curve pivots around CF, does not always hold was already reported for one ANF in Anderson et al 1971. Since then, it has been reported many times in mammals (e.g.…”
Section: Phase and Delaymentioning
confidence: 94%
See 1 more Smart Citation
“…PSTH peaks were separated in time by intervals equal to the inverse of the neuron's best frequency (BF), a 2π phase interval. Individual spike timing varied, consistent with phase locking (Anderson et al 1970;Sachs et al 1974;Joris et al 1994;Köppl 1997). For each intracellular recording, we quantified the temporal distance between the PSTH peaks.…”
Section: Multiples Of 2πmentioning
confidence: 99%